Comparison between right and left ventricular myocardia during the human fetal period. Stereological evaluation - Xavier-Vidal,Ricardo (1999)
PURPOSE: To develop a stereological comparison between right (RV) and left ventricle (LV) myocardium during the third human gestational trimester. METHODS: Five human fetal hearts of the third trimester provided representative samples of 5 RV myocardium and 4 LV myocardium. The material was fixed in 10% buffered formaldehyde, and processed through routine methods. Fifteen microscopic fields were randomly chosen and counted in each ventricular myocardium using an "M-42" test system. The following stereological parameters were assessed: Vv (%), Lv (µm²), Sv (µm²/µm³), Vp (µm³), Nv (1/mm³) and total N. RESULTS: No significant difference between the stereological parameters of the myocardial structures assessed was evidenced, when comparing RV and LV. CONCLUSION: Right and left human ventricular myocardium are very similar during the fetal period at least in regard to their structural aspects.